ANALISIS TINGKAT KEPUASAN NASABAH TERHADAP PELAYANAN ACCOUNT OFFICER PADA PROSES PERKREDITAN PT. BANK RAKYAT INDONESIA KANTOR CABANG SIGLI - Yuliana Yuliana; Bukhari Usman; Edwar M Nur; Rahmi Fitri Rizki (Departemen Manajemen, Universitas Syiah Kuala, 2019)
AbstractA company that performs well will always pay attention to the sustainability of its business. One of them is by carrying out continuous improvement with the aim of satisfying consumers or customers. The large number of banking companies in Indonesia has resulted in increasingly high competition, but only quality banks have survived to continue operating. The purpose of this study was to determine the extent of customer satisfaction with AO services at the Sigli branch of PT. BRRI in terms of five service dimensions, namely Reliability, Responsiveness, Assurance, Empathy, and Tangible. The sample in this study were 37 respondents. Data were analyzed using the Importance Performance Analysis (IPA) method. Service quality attributes that are considered important in determining customer satisfaction at the BRI Bank BRI branch are as many as 15 attributes. The results of the calculation of the level of customer satisfaction with AO services amounted to 92.73% of customers feeling satisfied with the service. The highest level of customer satisfaction lies in the professionalism attribute of AO services with a percentage of conformity level of 99.35%. While the lowest customer satisfaction lies in the good impression attribute given by AO to customers with a percentage of conformity level of 80.81%. KeywordsCustomer Satisfaction Level, and Accout Officer Service